ANALISIS STP (SEGMENTATION, TARGETING, POSITIONING) PADA LEMBAGA PENDIDIKAN XYZ - Sephy Lavianto (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
XYZ educational institution is an educational institution that has used technological developments as a step in developing a business. XYZ utilizes social media and websites as one of the supporters in campus introductions and finding new students. Social media that have been used, for example, such as Websites, Instagram and Facebook. In this study using qualitative descriptive research methods. This method focuses on answering research questions related to marketing strategy analysis in Increasing the Number of Students. This study also uses STP (Segmentation, Targeting, Positioning) analysis, a marketing model whose application involves three stages, namely segmenting the market, targeting the segments that are believed to be the most profitable and positioning the products sold in the most valuable way.